Poorer Sentence Reading Comprehension With Increased Reliance on Working Memory in Adults With Hearing Loss. - Ning, Ruijing; Marsja, Erik; Holmer, Emil (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Hearing loss (HL) has been associated with cognitive challenges, but its relationship with reading comprehension remains less explored. This study examined sentence reading comprehension in individuals with HL, focusing on two key questions: (a) Does HL lead to a shift in the cognitive mechanisms supporting sentence reading comprehension--specifically, increased reliance on working memory capacity (WMC) to compensate for reduced efficiency in accessing semantic long-term memory (sLTM)? (b) Is HL associated with reduced performance on sentence reading comprehension tasks? We investigated whether individuals with HL demonstrate lower sLTM access efficiency, poorer WMC, greater reliance on WMC for comprehension, and overall reduced comprehension performance compared to those with normal hearing (NH). Method: A total of 432 adults (215 with mild-to-severe HL, 217 NH) completed tasks assessing sentence reading comprehension, sLTM access, and WMC. Fluid intelligence and education were included as control variables. Multigroup structural equation modeling was used to compare latent constructs between groups and examine their relationships. Results: The HL group demonstrated lower sentence reading comprehension scores and less efficient sLTM access. No significant group difference was observed in WMC, but WMC had a stronger association with comprehension in the HL group than in the NH group. In both groups, sLTM access was important for comprehension performance. Conclusions: These findings suggest that sentence reading comprehension difficulties in individuals with HL may stem from reduced sLTM access efficiency and increased reliance on WMC, reflecting a shift in the balance between automatic retrieval processes and compensatory cognitive strategies. Interventions aimed at improving lexical retrieval may therefore support reading comprehension. Given the increasing reliance on reading as an alternative to auditory communication among this population, supporting reading skills may contribute to improved quality of life and independence among older adults.